Efek Fotodegradasi terhadap Chromophoric Dissolved Organic Matter (CDOM) dan Nutrien pada Air Danau - I Gusti Ngurah Agung Suryaputra (Universitas Pendidikan Ganesha, 2021)
This study's objective was to determine the effect of photodegradation on CDOM and nutrients in Lake Beratan, specifically in a tourism-dominated area. Subjects in this study are the water of Lake Beratan, while the object of this study is the absorbance CDOM, nutrient concentration, DO, pH, and temperature. We measured absorbance and nutrient concentrations using a Shimadzu UV-1800 UV-Vis Spectrophotometer. The spectral slope (S) and E2:E3 ratio were calculated from its absorbance. The result shows the possibility of misinterpretation due to the use of S or E2:E3 alone to express photodegradation. Either one demonstrates that photodegradation seems to decompose CDOM less than biodegradation. However, if we notice its absorbance value, it is clear that the opposite phenomenon, which is reasonable, takes place. We, therefore, conclude that CDOM photodegradation cannot be concluded from S and E2:E3 alone, but its absorbance is also necessary to lead to the right interpretation. Besides CDOM absorbance, photodegradation also affects nutrients in the water. Photodegradation decomposes organic materials into inorganics, whereas organic nitrogen is turned into ammonia and is then oxidised into nitrite and nitrate via nitrification. Overall, photodegradation decreases the concentration of nutrients dissolved in water.